Effects of exposure to nitrite on the antioxidant enzymes activity and the histopathological response of prawn Palaemonetes argentinus - Espino, Maria Laura (2015)
The aim of the present study was to determine lethal and sublethal effects of nitrite on the freshwater prawn, Palaemonetes argentinus (Nobili 1901). The 24, 48, 72 and 96 h median lethal concentration (LC50) of nitrite were found to be 103.07; 91.94; 82.39 and 62.53 mg L-1, respectively. The antioxidant activity of superoxide dismutase (SOD) was positively correlated with the concentration of nitrite in the environment, thus increasing the formation of hydrogen peroxide, substrate of catalase (CAT), which also showed an increased activity under the same experimental conditions. Histological samples showed that nitrite exposure caused hyperplasia, necrosis and changes in the lamellar epithelium in gills; while the effects in the hepatopancreas were degenerative desquamation, epithelial deterioration and hyperplasia. In conclusion, nitrite toxicity in P. argentinus increases with time of exposure. Moreover, this study proves that histological analysis of crustacean gills and/or hepatopancreas is a useful tool to determine the presence of toxic concentrations of nitrite in the water. Additionally, the measurement of the activity of antioxidant enzymes (e.g., SOD and CAT) as possible indicators of nitrite pollution should be considered in future studies.